Job Description of Public Health Officials in Nepal - Subedi, Sudarshan; MacDougall, Colin (Journal of Nepal Health Research Council, 2019)
Background: Job description of public health officials in Nepal has been prepared for assigning the definite role, responsibilities and authorities to exercise in different positions and circumstances. The purpose of this study was to analyse the job description of public health officials emphasizing the perspective of leadership and management.Methods: Document analysis method was used following the sequential process of skimming, reading and interpretation, and the themes were extracted by content analysis.Results: Job description of public health officials is mostly process and/or function oriented. Most of the officials are responsible for managing program and people rather than leading. Staff inspiration, motivation and encouragement, being one of the most important aspects of leadership, has been ignored in job description. District level officials are specifically assigned to manage programs and staff. As the position increases, the extent of practicing leadership increases and management decreases. Public health administrators have more leadership role as compared to public health officers; however, the proportion of management outweighs the leadership. Regional Directors have more leadership roles than other officials do. Conclusions: Role of public health officials vary from being a manager to a leader. Junior officials are predominantly the managers, mid-level officials are leadership-oriented managers, and top-level officials are leaders having managerial roles . In revising the job description (e.g., for the federal context), emphasis should be given to remove job duplication and role conflict, and should ensure role clarity, functions’ precision and output. Keywords: Document analysis; job description; leadership; Nepal; public health.